Affirmative Action and Enterprise Development in Malaysia: The New Economic Policy, Business Partnerships and Inter-Ethnic Relations - Edmund Terence Gomez (Kajian Malaysia, 2003)
Following the racial riots of l3 May 1969, the Malaysian government implemented an ambitious 20-year social engineering plan in l97l tcr achieve national unity. This plan, the New Economic poricy (NEp). sought to attain national unity by eradicating povcrty, irrespective of race. and restrucluring socicty so as to aehicvc inter-crhnic cconomic parity between the predominantly Malay Bumiputera (or 'sons of the soil') and the predominantly chinese non-Bumiputera. The govemment hoped to increase Btrmiputera corporate cqLrity ownership to 30% and reduce the poverty level to 15%by lgg0. wirh the end of the NEp, the National Development Policy (NDP), building on the objectives of its predecessor, was implemented between l99l and 2000